2017
DOI: 10.1590/s2179-975x12217
|View full text |Cite
|
Sign up to set email alerts
|

Periphytic community structure of Ostracoda (Crustacea) in the river-floodplain system of the Upper Paraná River

Abstract: Cite as: Higuti, J. et al. Periphytic community structure of Ostracoda (Crustacea) in the river-floodplain system of the Upper Paraná River. Acta Limnologica Brasiliensia, 2017, vol. 29, e120. Abstract: Aim:We assessed the effect of environmental factors on the structure of periphytic ostracods communities along the river-floodplain system of the Upper Paraná River. We predict that the higher distance from Porto Primavera dam downstream would lead to higher diversity and density of the ostracods. Methods: Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Comparatively, in South America, in flood plains of the Upper Parana River, species richness can be as high as 44 species (Higuti et al, 2017), interannually in this same system have been observed 38 species (Higuti et al, 2020), which is higher than that in lakes of Central America and comparable to richness of lakes in temperate regions. In Colombian aquatic systems, however, such as La Fé reservoir (Saldarriaga and Martínez, 2010) and River Magdalena basin (Roessler, 1990a, b) the number of species is again similar than that in Central America (⁓6 species per lake).…”
Section: Geology As Determinant Of Biodiversity and Distribution In The Northern Neotropicsmentioning
confidence: 57%
“…Comparatively, in South America, in flood plains of the Upper Parana River, species richness can be as high as 44 species (Higuti et al, 2017), interannually in this same system have been observed 38 species (Higuti et al, 2020), which is higher than that in lakes of Central America and comparable to richness of lakes in temperate regions. In Colombian aquatic systems, however, such as La Fé reservoir (Saldarriaga and Martínez, 2010) and River Magdalena basin (Roessler, 1990a, b) the number of species is again similar than that in Central America (⁓6 species per lake).…”
Section: Geology As Determinant Of Biodiversity and Distribution In The Northern Neotropicsmentioning
confidence: 57%
“…Although we do not intend to deeply evaluate taxonomic and ecological aspects for the northern Neotropical ostracodes in this study, we detected low species richness in the study area compared to that in South America and Europe. In the flood plains of the Upper Parana River, South America, species richness can be as high as 44 (Higuti et al, 2017), whereas in Europe, a single lake may host 32 species (Sluys, 1981;Lorenschat et al, 2014). This pattern may be influenced by sampling effort, as sampling sites did not always cover the lake extent.…”
Section: Geodiversity As a Determinant Of Distribution Of Freshwater ...mentioning
confidence: 99%
“…Freshwater ostracods are commonly found in temporary ponds and lakes, and their populations survive drought periods by producing resting eggs (Higuti et al, 2017;Rosa et al, 2021;Williams, 2006).…”
Section: Introductionmentioning
confidence: 99%